Thermal and electrical design of superconducting demonstrator for magnetic density separation. (1st June 2022) - Kosse, J J; Wessel, W A J; Zhou, C; Dhallé, M; Tomás, G; Krooshoop, H J G; ter Brake, H J M; ten Kate, H H J
Abstract: In this paper the focus is on thermal and electrical design aspects of a NbTi-based demonstrator magnet for magnetic density separation (MDS) that is being constructed at the University of Twente. MDS is a recycling technology that allows the separation of non-magnetic particles based on their mass density, using a vertical magnetic field gradient and a ferrofluid. To minimize the distance between the planar array of racetrack coils and the ferrofluid bath, the system is conduction-cooled. First the thermal design is presented, which shows that the coils can operate below 4.5 K with sufficient margin using a single cryocooler. High-purity aluminium heat drains enable a low thermal gradient across the cold mass. The current path is introduced, as well as the adopted protection scheme. The magnet's stored energy can safely be dumped in the coils. Diodes are placed (anti-)parallel to the coils in the cold to prevent high terminal voltages. In the case of a quench in the superconducting part of the current leads or an external anomaly, a switch is opened and the current is forced through a resistor in series with the diodes, causing a deliberate transition of the coils to the normal state and thus a fast ramp-down.